Grodek (1914) – le testament poétique de Georg Trakl - Natalia Teuber-Terrones (Recherches Germaniques)
Georg Trakl is one of the most commented-upon German-speaking poets. Certainly this timeless interest in him and his work can be explained by his complex personality—which can be seen as the archetypal ‘poète maudit’—and his unconventional biography but also by his mould-breaking poetry. His work is not only considered as the origin of ‘expressionist’ poetry, but also defined as ‘hermetic’ poetry by a lot of specialists. Above all, in front of this kind of complex and revolutionary poetry, we must ask the question about how to get an objective and scientific interpretation. How can we interpret a poem uniquely built on a muddle of images and figures with a heavy symbolic charge or, as some specialists say, codes? Dieter Lamping criticizes literary theory, because in his mind, the discipline is losing its original subject—literature—and only concerned with itself: theory. So, for Lamping modern poetry is the best way for literary theory to prove its validity. What especially defines modern poetry is the distance and destruction of traditional aesthetics and forms and in this context, literary theory must find its origins other than in aesthetic and formal characteristics, which means that the theory must find a deeper universal way to define why poetry is precisely poetry.